Children's Rights in War: ‘UNICEF's Role in Humanitarian Diplomacy in the Palestinian Crisis in the Gaza Strip’ - Lidya Elsye Yosefien Piris; Suryo Sakti Hadiwijoyo; Roberto Octavianus C Seba (Eduvest - Journal of Universal Studies, 2025)
Prolonged conflict in the Gaza Strip has created a humanitarian emergency that disproportionately affects children, who are among the most vulnerable to violence, displacement, and deprivation of fundamental rights. In response to these challenges, this study aims to analyze the role of the United Nations Children’s Fund (UNICEF) in humanitarian diplomacy, particularly regarding protecting and fulfilling children’s rights amid the Palestinian crisis. Using a qualitative descriptive method, data were collected through literature reviews and official documentation to explore how UNICEF integrates human security principles into its diplomatic and operational strategies. The findings show that UNICEF not only acts as a humanitarian aid provider but also serves as an active diplomatic actor advocating for child protection through negotiation and collaboration with both state and non-state actors. The study concludes that UNICEF's dual role—operational and diplomatic—is crucial in promoting a safer and more dignified life for children in Gaza. The implications of this research underline the need for international support and policy reinforcement to enhance UNICEF’s humanitarian efforts. These insights are valuable for academics, policymakers, and practitioners involved in international humanitarian work, especially in conflict-affected regions.